Consequences of the Rise in Female Labor Force Participation Rates: Questions and Probes - Michael, Robert T. (Journal of Labor Economics, 1985)
This paper discusses three independent inquiries into consequences of the rise in women's labor force participation rate (LFPR) in the United States since 1946. (1) The growth in women's LFPR is decomposed by decade, age, marital status, presence of age-specific children, and years of schooling. (2) Evidence on the impact of the growth on the inequality in income among husband-wife families is summarized and the impact on income inequality in other family structures is discussed. The effect on the level of family real income is considered and "money illusion" in measuring the change in income is noted. (3) Bivariate autoregressive time series are estimated with annual data from 1950 to 1980, indicating that lagged values of women's LFPR are systematically correlated with measures of flow fertility, marriage, schooling, and men's income, while only fertility has a strong, persistent lagged correlation with LFPR.